Implementation of Extracurricular Dance to Develop Students' Talents and Interests in The Field of Arts - Susilowati, Retno (Al Hikmah: Journal of Education, 2024)
The purpose of this study is to describe the implementation of extracurricular activities to develop students' talents and interests in the arts at MI Darul Ulum 02. The research method is descriptive qualitative research. Data collection techniques were carried out through interviews, observation and documentation. The existing data is analyzed by performing data reduction and concluding the data.  The results of this study are that the implementation of extracurricular dance is carried out by students from grade I to grade IV. The songs used use dolanan songs such as jaranan, cublak-cublak suweng, and mushrooman. The supporting factors in this study were that students felt happy and enthusiastic in carrying out dance activities. The inhibiting factor is that some students have difficulty understanding the material that has been delivered by the trainer. Therefore, it is necessary to evaluate and add hours in the implementation of extracurricular dance activities.